Lobbying on the IASB Standards: An analysis of the Lobbyists’ Behaviour over Period 2006–2014 - Procházka, David (Copernican Journal of Finance & Accounting, 2015)
The paper investigates whether there is any significant difference in lobbying behaviour on the IASB’s projects depending on the type of a project. In particular, we scrutinise the differences in number of comments letters received for: (a) major vs. minor projects; (b) projects successfully completed after the exposure draft phase vs. projects revised/stopped after the exposure draft phase. To test our two hypotheses about the pattern of lobbyist behaviour, we use reasoning based on a rational lobbying model developed by Sutton (1984). Our paper limits the scope to the IASB’s projects on its agenda over period 2006–2014; we thus complement previous studies of Kenny & Larson (1995) and Jorissen et al. (2012), who analysed the lobbying on IASB’s standards over periods 1989–1992, and 2002–2006 respectively. Our results show that the IASB inclines to succumb to the pressure of lobbying parties if the lobbying is quite massive (measured by number of comment letters submitted) in relation to other projects. We supplement the literature on lobbying on accounting standards with additional evidence on general ability of the lobbyist to influence the decision of standard- -setters by pushing them to revise a project substantially, or even to stop the project in question completely.